Patients' Satisfaction about Health Services in Out-patients Clinics of Teaching Hospitals in Erbil City - Ibrahim Hasan Mustafa; Ako Ramadan Satar (Erbil Journal of Nursing and Midwifery, 2019)
Background and objectives: Outpatients' satisfaction is important aspect to evaluation levels of quality and quantity services provided in outpatients departments. The study aimed to assess patients' satisfaction toward health care provided in out-patients clinics of Rizgary and Hawler Teaching Hospitals and find out the factors that are associated with levels of satisfaction. Methods: A cross-sectional study was conducted in Hawler and Rizgary Teaching Hospitals in Erbil city. The study started from April 1st, 2017 to July 1st, 2017. A convenience method of sampling was used to recruit 500 participants who attended in Out-patients Clinics 238 (47.6%) from Rizgary Hospital, and 262 (52.4%) from Hawler Hospital. The questionnaire format was designed by researches for data collection. The questionnaire consisted of two parts: part one socio-demographic and hospitalization data and part two included 59 questions about health care services. Five points Likert scale was used to assess patients' satisfaction. The Statistical Package for the Social Sciences, version 22 was used da-ta enter and analysis. A chi-square test of association was used to compare proportion. Results: The study found 27.8% of patients were satisfied, with respect to all health services (including physicians, nurses, pharmacies, and laboratories) and in health aspects (including communication, maintain for privacy of patients and respect them, counseling and advising roles, and time spend with patients) . There was an association between patients' satisfaction and age categories, levels of income, and the number of visits to outpatient departments. Conclusions: The majorities of outpatients have no idea regarding satisfaction or not satisfied with health services in outpatients departments of major hospitals in Erbil city. There were significant association between the level of satisfaction with age, level of income and hospital.